Distribution and sources of particulate organic matter from the anthropogenically disturbed Iyidere River to the Black Sea coast - Kaymak, Nehir; Mutlu, Tanju; Verep, Bulent (Frontiers in Environmental Science, 2023)
Understanding the biogeochemical processes of particulate organic matter occurring in the river under anthropogenic disturbances and its transport to the coastal system is important for environmental resource management. In this study, we investigated the sources and distribution of particulate organic matter (POM) from the upper reaches of the Iyidere River, Türkiye, to the coastal water of the Black Sea during the fall and spring seasons using elemental (POC and PON (%), C/N), isotopic (δ13C and δ15N) and Bayesian mixing model (MixSIAR) analysis. The POC (%), PON (%), and C/N of POM varied seasonally, indicating that the composition of POM varied with river hydrology, which varies depending on the climate of the region. Both the mixing model and the isotopic and elemental ratios of POM have revealed that the organic matter sources contributing to the riverine POM, during the fall season, when the precipitation is severe, exhibited a uniform distribution. Heavy rain increased soil erosion along the high-slope land, and as a result, soil and bacteria were identified as the main contributor of POM along the Iyidere River. The results showed that the organic matter sources contributing to POM in the spring season showed significant spatial variation. Terrestrial vegetation, soil OM and bacteria were the main contributors of POM depending on sites and these contributions did not show a regular trend along the river. δ15N of POM had significant spatial variation in both seasons that was likely caused by nitrogen inputs derived from anthropogenic activities along the river. The anthropogenic activities and cascade dams causing variations in the contribution of organic matter to the POM are the likely important driving factors in this river-coastal system.